Skin Pathology Laboratory of the Department of Dermatology of Hospital de Santa Maria (Lisbon). Twelve Years of Activity (2008-2019) – Part II: Non-Tumour Diseases - de Vasconcelos, Pedro (2021)
Introduction: Between 2008 and 2019, in the Skin Pathology Laboratory of the Dermatology Department of Hospital de Santa Maria (Lisbon), 60 741 histological exams were performed, 11 873 of them concerned non tumour diseases (20%). Material and Methods: A retrospective study was conducted through the analysis of the histological exams of the non-tumoral skin pathology of the laboratory between January 2008 and December 2019. Results: Toxic erythemas were the most frequent group diagnosed (16%), followed by spongiotic dermatosis (14%), cutaneous infections (14%), psoriasiform dermatosis (10%) lichenoid dermatosis (8%), autoimmune bullous skin diseases (7%), vasculopathies (7%), collagenosis (6%), granulomatous diseases (5%), non tumour skin adnexal diseases (4%), panniculitis (1%), non tumour mucosal diseases (1%) and genodermatoses (1%). A number of cases (6%) corresponded to many diverse diagnoses that could not be classified into the main groups considered. Conclusion: Comparing with two previous series concerning the activity of this laboratory (referring to the period between 1975-1980 and 1998-2007), it was noticed that the total number of exams that were done in the considered period had consistently grown. This global growth was seen in all pathological categories, with the exception of genodermatoses. The observed results reaffirm the relevant role of the Skin Pathology Laboratory in the context of the Dermatology Department of Hospital de Santa Maria (Lisbon), not only based on the volume of exams there processed but also due to the higher level of expertise it achieved.